Taenia solium DNA is present in the cerebrospinal fluid of neurocysticercosis patients and can be used for diagnosis - Almeida, Carolina R.; Ojopi, Elida P.; Nunes, Caris Maroni [UNESP]; Machado, Luis R.; Takayanagui, Osvaldo M.; Livramento, Jose A.; Abraham, Ronaldo; Gattaz, Wagner F.; Vaz, Adelaide J.; Dias-Neto, Emmanuel (Dr Dietrich Steinkopff Verlag, 2006)
Neurocysticercosis is the most frequent parasitic infection of the CNS and the main cause of acquired epilepsy worldwide. Seizures are the most common symptoms of the disease, together with headache, involuntary movements, psychosis and a global mental deterioration. Absolute diagnostic criteria include the identification of cysticerci, with scolex, in the brain by MRI imaging. We demonstrate here, for the first time, that T. solium DNA is present in the cerebrospinal fluid of patients. The PCR amplification of the parasite DNA in the CSF enabled the correct identification of 29/30 cases (96.7 %). The PCR diagnosis of parasite DNA in the CSF may be a strong support for the diagnosis of neurocysticercosis.
Keywords: PCR; CSF; neurocysticercosis; Taenia solium; liquor